한국 성인의 수산물 섭취와 불면증 및 심혈관 질환의 관련성 연구: 한국인 유전체 역학 조사 사업 자료를 기반으로 - 김민지(Minji Kim); 정영은(Yeongeun Jeong); 정유나(Yuna Jeong); 장원(Won Jang); 김세인(Sein Kim); 김양하(Yangha Kim) (Journal of nutrition and health, 2024)
Purpose: Accumulating evidence suggests that seafood and its components, such as eicosapentaenoic acid and docosahexaenoic acid, are known to prevent cardiovascular disease (CVD). However, little is known about whether sleep quality, which has been recognized as a risk factor for CVD, might influence these associations. Therefore, the purpose of the study was to investigate the longitudinal associations between seafood consumption and CVD in Korean adults with or without insomnia. Methods: The data were collected from the Korean Genome and Epidemiology Study (KoGES) and included 3,168 participants aged 40-69 years. Dietary intake was measured by a validated 106-item food-frequency questionnaire, and insomnia was assessed using a questionnaire on sleep-related symptoms. The CVD events included myocardial infarction, coronary artery disease, congestive heart failure, cerebrovascular disease, and peripheral vascular disease. Associations of seafood consumption with CVD were assessed using time-dependent Cox regression analyses to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) while adjusting for potential confounding factors. Results: During the 8-year follow-up period, the incidence of CVD was 5.1%. There was a positive association between seafood consumption and most food groups, as well as nutrients. In contrast, as seafood consumption increased, the consumption of grains decreased. Regarding nutrient intake, there was a negative association between seafood consumption and carbohydrate intake. After adjustment for confounding factors, the risk of CVD was inversely associated with seafood consumption, with a 56% lower risk (HRT3 vs. T1, 0.44; 95% CI, 0.26-0.75; p = 0.002), only in the non-insomnia group. Conclusion: Findings from this study suggest that seafood consumption might lead to more favorable outcomes against CVD if accompanied by good sleep quality. 본 연구는 한국인 유전체 역학 조사사업 자료를 활용하여 40-69세 한국 성인 남녀를 대상으로 8년간의 추적 기간 동안 수산물 섭취와 심혈관 질환과의 관련성에 대해 불면증 여부에 따라 분석하였다. 수산물 섭취량이 높을수록 열량을 비롯한 대부분의 식품과 영양소 섭취량이 높았으나, 곡류 및 탄수화물의 섭취량은 낮았다. 또한, 불면증이 없는 대상자에게서 수산물의 섭취량이 높을수록 심혈관 질환의 발생 위험이 낮았다. 따라서 수산물의 섭취와 더불어 수면의 질이 개선될 때 심혈관 질환의 위험을 감소시키는데 보다 효과적일 것으로 사료된다. 이에 관한 연구는 거의 없는 실정이기 때문에 수산물 섭취와 심혈관 질환 발생의 관련성에 있어 적절한 수면의 질이 영향을 줄 수 있다는 본 연구의 시사점을 토대로 추후 연구가 필요하다.